Nope [videorecording (DVD)] - Peele, Jordan, 1979-; Kaluuya, Daniel, 1989-; Palmer, Keke; Yeun, Steven; Wincott, Michael, 1958-; Perea, Brandon, 1995-; Schmidt, Wrenn; Ferreira, Barbie, 1996-; Notary, Terry; Graye, Devon, 1987-; Mills, Donna; Perkins, Oz, 1974-; et al. (Universal, 2022)
Two siblings who run a California horse ranch discover something wonderful and sinister in the skies above, and the owner of an adjacent theme park tries to profit from the mysterious, otherworldly phenomenon.